New local health officials: health departments’ newest leaders - Kirkland, Chelsey; Westfall, Noah Yee; Patel, Krishna; McCall, Timothy C.; Leider, Jonathon P. (Frontiers in Public Health, 2025)
IntroductionThe purpose of this descriptive study was to compare the demographics of new and experienced local health officials (LHOs) and the rurality and size of the local health departments (LHDs) they serve.Materials and methodsDescriptive characteristics of new LHOs and experienced LHOs were compared between two national public health workforce datasets: the 2021 Public Health Workforce Interest and Needs Survey (PH WINS) and the 2022 National Association of County and City Health Officials (NACCHO) National Profile of Local Health Departments study (Profile). The 2022 Profile study was fielded from July through September 2022 from a population of 2,512 LHDs across the US. The 2021 PH WINS survey was fielded to a nationally representative sample of state health Agency-Central Offices and LHD staff. Descriptive characteristics were computed comparing new LHOs with experienced LHOs based on work status, age, gender, race/ethnicity, education level, rurality and size of the jurisdiction.ResultsApproximately 30% of all LHOs are new (<2 years of experience) with no difference among jurisdiction sizes or rurality. Compared to experienced LHOs, a slightly greater proportion of new LHOs identified as Native American, Black, or Asian, and are younger.DiscussionProviding professional supports to new LHOs and addressing recruitment and retention challenges facing public health leadership can help ensure that the senior executive level of the public health workforce reflects the diverse and varied populations that it serves.